Europe's Farm to Fork Strategy and Its Commitment to Biotechnology and Organic Farming: Conflicting or Complementary Goals?. (June 2021) - Purnhagen, Kai P.; Clemens, Stephan; Eriksson, Dennis; Fresco, Louise O.; Tosun, Jale; Qaim, Matin; Visser, Richard G.F.; Weber, Andreas P.M.; Wesseler, Justus H.H.; Zilberman, David
Abstract : The European Commission's Farm to Fork (F2F) strategy, under the European Green Deal, acknowledges that innovative techniques, including biotechnology, may play a role in increasing sustainability. At the same time, organic farming will be promoted, and at least 25% of the EU's agricultural land shall be under organic farming by 2030. How can both biotechnology and organic farming be developed and promoted simultaneously to contribute to achieving the Sustainable Development Goals (SDGs)? We illustrate that achieving the SDGs benefits from the inclusion of recent innovations in biotechnology in organic farming. This requires a change in the law. Otherwise, the planned increase of organic production in the F2F strategy may result in less sustainable, not more sustainable, food systems. Highlights: Sustainable food systems will require profound changes in people's consumption patterns and lifestyles, which is true regardless of the farming methods used and does not change the fact that organic farming often requires more land than conventional farming for the same quantity of food output. Some features of organic farming in the EU contribute to the Sustainable Development Goals (SDGs); other features may jeopardize the achievement of SDGs 2, 13, and 15. The negative indirect effects of additional land-use change may outweigh the positive direct effects on global climate and biodiversity, so that a large-scale switch to organic farming in the EU could possibly turn out to be a disservice to global sustainability. Achieving the SDGs would benefit from the inclusion of biotech innovations in organic farming. The implementation of required changes in the EU law is unlikely under current political realities but is nevertheless recommended from a scientific perspective.